Waterlogging severely retards P use efficiency of spring barley (Hordeum vulgare) - Ylivainio, Kari; Jauhiainen, Lauri; Uusitalo, Risto; Turtola, Eila (Wiley, 2018)
Efficient utilization of various phosphorus (P) sources for producing optimum yields in P-deficient conditions requires knowledge of best management under changing weather conditions. In this study, barley (Hordeum vulgare) was grown in an extremely P-deficient soil with variable moisture conditions. During a wet growing period, utilization of P from dairy cow manure (DCM), fox manure (FM) and meat and bone meal (MBM) was compared with the utilization of P from superphosphate (SP) with concomitant effects on grain yield and quality. High P application rates were necessary to compensate for severe yield losses due to waterlogging. Only 7 kg P/ha was required for optimum yield in less waterlogged conditions, while 43 kg P/ha was needed in waterlogged conditions. In both moisture conditions, broadcast DCM-P increased grain yield similar to banded SP-P, although P acquisition was lower in early growth stages. FM-P and MBM-P were less efficiently utilized. Waterlogging also depressed yield quality when P was applied. Extreme rainfall events are predicted to become more frequent at northern latitudes. As an alternative to higher P fertilizer rates, improving soil drainage could be a favourable, longterm measure for better utilization of applied P and soil P resources, even at very low soil P status.
Keywords: root growth; soil test P; yield quality; nutrient uptake; roots; growth; soil analysis; yields